2018
DOI: 10.3390/recycling3040048
|View full text |Cite
|
Sign up to set email alerts
|

A Voluntary Delivery Point in Reverse Supply Chain for Waste Cooking Oil: An Action Plan for Participation of a Public-School in the State of Rio De Janeiro, Brazil

Abstract: Improper disposal of waste cooking oil into sewer systems is harmful to the environment. Through the selective collection, this highly polluting residue can be handled in a less harmful way. The present study presents an action plan for a public school in the Region of Médio Paraíba Fluminense of the state of Rio de Janeiro, Brazil to serve as a voluntary delivery point in a reverse logistics chain for waste cooking oil. A case study method with semi-structured interviews was carried out with agents who are pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, from a social perspective, door-to-door collections and collections through schools are more sustainable. In fact, recent pilot studies to collect dUCO from schools have shown that interest is great and if sustained, schools can successfully become collection hubs for dUCO [24]. However, none of these pilot systems have managed to maximize the social and environmental benefit associated with utilizing schools as the starting point of the reverse logistics chain, as their application remained at the pilot stage, not having yet managed to overcome the bottlenecks associated with dUCO collection.…”
Section: Discussionmentioning
confidence: 99%
“…However, from a social perspective, door-to-door collections and collections through schools are more sustainable. In fact, recent pilot studies to collect dUCO from schools have shown that interest is great and if sustained, schools can successfully become collection hubs for dUCO [24]. However, none of these pilot systems have managed to maximize the social and environmental benefit associated with utilizing schools as the starting point of the reverse logistics chain, as their application remained at the pilot stage, not having yet managed to overcome the bottlenecks associated with dUCO collection.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing PPP for developing RSC is a ubiquitous recommendation in the waste literature [64][65][66]. The use of solid partnerships with the government for establishing a RSC is a basic requisite as private CDW related organizations need regulatory and financial support to operate efficiently [1].…”
Section: Promoting a Local Cdw Rscmentioning
confidence: 99%